Improvement of jet lag and travel fatigue symptoms and their association with prior international travel experience in junior athletes - Tsukahara, Y.; Kamada, H.; Torii, S.; Yamasawa, F. (Sports, 2024)
Jet lag and travel fatigue can occur after crossing multiple time zones in a short period of time, possibly affecting various aspects of an athlete`s behavior. However, there are few studies regarding this issue, particularly considering junior athletes. This study aimed to investigate and quantify the symptoms of jet lag and travel fatigue and the factors impacting these conditions. A survey was completed by 41 Japanese junior athletes (21 men and 20 women), competing at an international game in Finland, to assess their performance, sleeping habits, digestion, fatigue, and jet lag on the first day of arrival and on the opening day of the competition. Although athletes awoke less often during sleep on the opening day of the competition compared with the first day, sleep time, ease of falling asleep, and sleep quality decreased significantly. Prior experience traveling abroad for international competitions was positively associated with improvements regarding ease of falling asleep (coefficient = 2.22, p = 0.01), quality of sleep (coefficient = 2.16, p = 0.02), and alertness after waking up (coefficient = 1.85, p = 0.05) by the opening day of the competition when compared with the results for athletes who had no such prior experiences. Junior athletes experience symptoms of jet lag and travel fatigue that may persist until the day of competition, and prior experience traveling abroad may help in alleviating their symptoms.